2016
DOI: 10.1108/ijcst-01-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of structure and air permeability of aromatherapic terry textile

Abstract: Purpose – The purpose of this paper is to investigate the physical properties of smart aromatherapic ramie/cotton terry fabrics containing microcapsules (MC) with essential Eucalyptus oil. Design/methodology/approach – Terry fabrics are manufactured by changing the weft density. The air permeability is determined for grey and microencapsulated textile. The factorial designs are made. For informative experiment the linear type of regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Typical SEM images of microcapsules: (a) with eucalyptus essential oil and (b) in aroma finished ramie/cotton terry fabric after 5 cycles of washing and drying procedures …”
Section: Main Features Of Microencapsulation and Microcapsulessupporting
confidence: 61%
See 2 more Smart Citations
“…Typical SEM images of microcapsules: (a) with eucalyptus essential oil and (b) in aroma finished ramie/cotton terry fabric after 5 cycles of washing and drying procedures …”
Section: Main Features Of Microencapsulation and Microcapsulessupporting
confidence: 61%
“…In this research, scanning electron microscope (SEM) images confirmed about effective applications of the aforementioned microcapsules. Further studies on ramie/cotton terry fibrous products containing microcapsules with eucalyptus essential oil were reported by Petrulyte et al . and Vankeviciute et al .…”
Section: Microcapsules For Cosmetic and Medical Fibrous Materialsmentioning
confidence: 79%
See 1 more Smart Citation
“…Firstly, physical finishing technique was used to dispose the fabrics. The fabric was placed in the water bath (HH-8, Ningbo Textile Instrument Factory, China) under certain immersion temperature (20,35,50, 65, 80°C) and time (30, 60, 90, 120, 150 min). Then it was pressed by two rollers to squeeze out excess water in the fabric.…”
Section: Processing Of Shrink Resistant Finishingmentioning
confidence: 99%
“…The microcapsules can be applied by stamping works, exhaustion dyeing, impregnation, spraying and coating. Besides, microcapsules can be incorporated in the fiber directly without modifying its touch and color [27][28][29][30][31][32][33][34][35][36][37][38][39]. The microencapsulation of essential oils has led to many novel applications, including children's garments, hosiery, sheets, towels, cushions, fragrant ties and shoe insoles, as a consequence not only of the pleasant smell of the essential oils released but also of the wide variety of therapeutic benefits.…”
Section: Introductionmentioning
confidence: 99%